Parenting for lifelong health programme for parents and teens in Botswana: cost estimation and the budget impact analysis - Ntuli, Musa (Health Economics Unit, 2025)
Background: Given all its detrimental effects, child abuse is one of the biggest public health issues. Depression, suicidal thoughts, risky sexual behaviour, and substance abuse are a few examples of these effects. The random control trial was conducted in 25 nations with low to middle incomes, including Botswana. The goal of the PLH SUPER study is to address and stop child abuse in environments with limited resources. The overall and unit costs of the PLH program and the BIA, should it expand to national levels, were estimated by this PLH SUPER sub-study. Methodology: Micro-cost analysis was performed from April 2021 until March 2022, taking the provider perspective to make a computation on the total and unit costs of enrolling families in the PLH program. The target population of the teenagers of age 10–17 and their guardians were the aimed group in Botswana, and the BIA was subsequently determined through the unit cost per family enrolled. Results: The results exposed variation in every PLH program implementation cost across centres, from US $22,771.96 in Goodhope, to US $60,662.82 in Gaborone. The unit cost per enrolled family ranged from US $168.68 in Goodhope, to US $336.91 Letlhakane. Personnel costs accounted for 64% of total expenditure. The PLH enrolment coverage projected at 5.7% and 40,525 families identified as the programs target population for national scale-up. The cost per family enrolled in the PLH program ranged from US $168.68 to US $336.91, per family. Therefore, the total budget needed for expanding the PLH program varies from US $6,835,788.61 to US $13,653,186.67 Conclusion: This study investigated the cost implication of nationally scaling-up PLH interventions in Botswana. The findings of this study present the decision makers with guidance on the possible costs that could be incurred in scaling-up the PLH interventions countrywide. Furthermore, the study also guides policy makers on how the national scale-up could impact the existing health and wealth budget. This study immensely contributes on the global discourse on prevention of maltreatment. Lastly, Cost Effectives Analysis study for rolling out PLH interventions in Botswana is highly recommended.